Assessment of physical demands and fluid balance in elite female handball players during a 6-day competitive tournament - Cunniffe, B.; Fallan, C.; Yau, A.; Evans, G. H.; Cardinale , M. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
Little data exists on drinking behavior, sweat loss, and exercise intensity across a competitive handball tournament in elite female athletes. Heart rate (HR), fluid balance and sweat electrolyte content were assessed on 17 international players across a 6-day tournament involving 5 games and 2 training sessions played indoors (23 ± 2 °C, 30 ± 2% relative humidity). Active play (effective) mean HR was 155 ± 14 bpm (80 ± 7.5% HRmax) with the majority of time (64%) spent exercising at intensities >80% HRmax. Mean (SD) sweat rates during games were 1.02 ± 0.07 L/h and on 56% of occasions fluid intake matched or exceeded sweat loss. A significant relationship was observed between estimated sweat loss and fluid intake during exercise (r2 = .121, p = .001). Mean sweat sodium concentration was 38 ± 10 mmol·L, with significant associations observed between player sweat rates and time spent exercising at intensities >90% HRmax (r2 = .181, p = .001). Fluid and electrolyte loss appear to be work rate dependent in elite female handball players, whom appear well capable of replacing fluids lost within a tournament environment. Due to large between-athlete variations, a targeted approach may be warranted for certain players only